STRUCTURAL GENERALITY OF UZBEK LANGUAGE CLAUSES - Sayfullaeva, Ra’no; Kadirovna, Abuzalova Mekhriniso (International Journal of Psychosocial Rehabilitation, 2020)
Speech variants of Uzbek language clauses are many-sided, despite it their structure and principles of word-connection submit to the general for all grammar requirements. [WPm] – minimum structural model of Uzbek language clauses. Theory that, the forms of the category of predicativity are obligatory structural elements of Uzbek language clause is proved in the article. On its basis becomes conclusion about syntactic essence of the given category in Turkic languages.